Pattern of Hematological Manifestations in Patients with Systemic Lupus Erythematosus Attending in a Tertiary Care Hospita (Journal of Medicine, 2017)
Background: Hematological manifestations are not uncommon with systemic lupus erythematosus (SLE). Some of them are life-threatening, warranting prompt action, while others need special consideration. This study aimed at pattern of hematological manifestations in patients with SLE.Materials and Methods: This descriptive cross sectional study included patients who were diagnosed and treated as SLE at Dhaka Medical College Hospital. Detailed history and physical examinations were performed in every patient. SLE was diagnosed as per ACR criteria. Necessary investigations were carried out. Hematological manifestations were scrutinized and statistically analyzed.Results: A total of 89 patients (97.8% females, mean age 24.86 ±5.88 years) were studied. Hematological manifestations were present in 77 (85.4%) patients at the time of diagnosis. Among them anemia was most frequent in 77.5% patients followed by neutropenia (19.1%), lymphopenia (17.9%), thrombocytopenia (17.9%), autoimmune hemolytic anemia (AIHA) in 10.1% and pancytopenia in 5.6% patients. Normocytic normochromic anemia (NNA) was the most common peripheral blood film (PBF) findings found in 31 (34.8%) of the patient, followed by microcytic hypochromic anemia (MHA) (32.6%).Conclusion: Hematological manifestations are frequently encountered in SLE. A sound conception about the relative frequency of hematological manifestations associated with systemic lupus erythematosus will help the clinician to take necessary measures for the wellbeing of the patient.J MEDICINE July 2017; 18 (2) : 86-91